The Computer-Animated Film : Industry, Style and Genre - Holliday, Christopher (Edinburgh University Press, 2022)
Re-frames the computer-animated film as a new genre of contemporary cinemaWidely credited for the revival of feature-length animated filmmaking within contemporary Hollywood, computer-animated films are today produced within a variety of national contexts and traditions. Covering thirty years of computer-animated film history, and analysing over 200 different examples, The Computer-Animated Film: Industry, Style and Genre persuasively argues that this body of work constitutes a unique genre of mainstream cinema. Informed by wider technological discourses and the status of animation as an industrial art form, the book not only theorises computer-animated films through their formal properties, but connects elements of film style to animation practice and the computer-animated film's unique production contexts.Key FeaturesProvides a wide-ranging focus on a multitude of animation studios, companies, facilities, divisions and subsidiaries in Hollywood and beyondSupported throughout by close textual analysis and clearly marked case studiesExpands the critical examination of computer-animated films by combining animation and film theory together with theories of animation practice, industry papers and original studio production memosCase StudiesShark Tale (2004)Hoodwinked! (2006)Flushed Away (2006)Over the Hedge (2006)The Good Dinosaur (2015)Frozen (2013)Zootopia (2016)Ratatouille (2007)Antz (1998)A Bug's Life (1998)Wall-E (2008)Toy Story 3 (2010)Toy Story 2 (1999)Cars (2005) / Cars 2 (2011)Happy Feet (2006)Sausage Party (2016)Monsters, Inc. (2001)Rise of the Guardians (2012)Despicable Me 2 (2013) / Minions (2015)Surf's Up (2007)Bolt (2008)